Shoot 'em up [videorecording (Blu-Ray)] - Montford, Susan; Murphy, Don, 1962-; Benatar, Rick; Davis, Michael, 1961 August 1-; Owen, Clive; Giamatti, Paul; Bellucci, Monica, 1968-; McHattie, Stephen (New Line Home Entertainment, 2008)
A mysterious man known only as Smith teams up with a gorgeous streetwalker to protect a newborn baby from a determined hitman. The three are swept into a deadly game of cat-and-mouse through the bowels of the city.